Analisis Sentimen Publik TikTok dengan Pendekatan Lexicon-Based: Studi Kasus Timnas Indonesia di Piala Dunia 2026 - Hamzah Nurrifqi Fakhri Fikrillah; Galih Pratama Herawan Putra; Fikri Chairul Ummam (Jurnal Kendali Teknik dan Sains, 2026)
Football in Indonesia is not merely a sport but a social phenomenon that triggers massive public emotional engagement. Every result of the Indonesian National Team, particularly in prestigious events such as the FIFA World Cup Qualifiers, often generates waves of opinion in digital spaces filled with criticism, support, and disappointment. The failure of the Indonesian National Team in the 2026 FIFA World Cup Qualifiers has become an important momentum to systematically understand public perception. The purpose of this study is to identify the distribution of public sentiment and to reveal the main issues most frequently discussed through keyword visualization, thereby providing an overview of societal reactions. This research utilizes 971 comments from the TikTok platform as the primary dataset, collected through a crawling process and processed using text mining stages before being classified with a sentiment analysis method. The findings indicate a sentiment distribution dominated by Neutral at 63.67%, Negative at 32.36%, and Positive at 3.97%. The word cloud visualization highlights dominant keywords such as “Pecat” (Dismiss), “Evaluasi” (Evaluation), and “PSSI” (Indonesian Football Association), reflecting public criticism of managerial aspects, although positive words such as “Semangat” (Spirit) and “Dukung” (Support) also appear, emphasizing supporter loyalty. These results contribute to an empirical understanding of the issues most highlighted by the public and the distribution of collective emotions, which can serve as a basis for PSSI and stakeholders in formulating communication strategies, policy evaluations, and improvements to the national football management system.